Prevalence of nutritional deficiencies among school going adolescents of Vadodara, Gujarat, India: a cross sectional study - Bhalsod, Ashish Shamjibhai; Dave, Nisarg N.; Thakor, Nilesh (International Journal of Advances in Medicine, 2019)
Background: Adolescent constitutes over 23% of the population in India. Critical development occurs during adolescence period. Growth spurt and increase in physical activity during adolescent period increases the nutrition and health needs of the adolescent. Objective was to study prevalence of nutritional deficiencies among school going adolescents of Vadodara city, Gujarat. Methods: The study was carried during period from September 2018 to August 2019. After taking the permission of principals of 3 schools and consent of the parents of adolescents, 511 adolescents from 3 schools of Vadodara city were examined for signs of various nutritional deficiencies. The data was collected by predesign, pretested proforma and analyzed using SPSS 17.0 (Trial Version). Results: Out of total 511 adolescents 253(49.5%) were female. Mean age of the study adolescents was 15.6±1.81 years. Maximum numbers of the adolescents were in the age group of 10-14 years (60.3%). Mean age of female and male adolescents was 15.2±1.71 years and 15.6±2.01 years respectively. The study revealed that vitamin A deficiency was present in 38(7.4%) adolescents. Vitamin B complex deficiency signs were seen in 112(21.9%) adolescents. Vitamin C deficiency signs were seen in 43(8.4%) adolescents. Protein Energy Malnutrition was observed in 52(10.1%) adolescents. Essential fatty acid deficiency was observed in 56(10.9%) adolescents. Conclusions: High prevalence of nutritional deficiencies among these adolescents needs great attention and health education.